Modelagem e simulação do sistema de evaporadores de miscela de uma destilaria de óleo de soja - Prado, Eduardo Rasi de Almeida (2013)
The process for obtaining soybean oil is one of the most important sectors of Brazilian agroindustrial complex, consisting the steps of drying, preparation, extraction, distillation and solvent recovery. Its products are used in steel mills, cosmetic industries and their raw material in the production of food for human consumption. With the growth of industrial production of soybean oil, reducing costs and waste is essential for an industry to be competitive in the global market. This cost reduction can occur in the distillation step, which is one of the largest energy consumption of this process, which is constituted by three evaporators and a "stripper" and is intended to separate the crude oil from the hexane solvent by heating the mixture. In this context, modeling and process simulation using simulators such as HYSYS, becomes attractive due to the possibility of analyzing a cost reduction of steam, it is the input with the highest amount paid in manufacturing cost. Developed a model for soybean oil to the micelle and the micelle system evaporators, which was validated with the actual data of a process and values found in the literature. The results obtained in HYSYS, showed that modeling and simulation using HYSYS are consistent with the actual process conditions and near to the values found in the literature, can be used as a tool for analysis and simulation of micelle concentration step of the evaporators in process of obtaining soybean oil, disponbilizando the analysis process, prior to any physical changes in the distillation process may occur a large investment without generating an expected return.